2009
DOI: 10.1377/hlthaff.28.1.179
|View full text |Cite
|
Sign up to set email alerts
|

What Works In Chronic Care Management: The Case Of Heart Failure

Abstract: ABSTRACT:The evidence base of what works in chronic care management programs is underdeveloped. To fill the gap, we pooled and reanalyzed data from ten randomized clinical trials of heart failure care management programs to discern how program delivery methods contribute to patient outcomes. We found that patients enrolled in programs using multidisciplinary teams and in programs using in-person communication had significantly fewer hospital readmissions and readmission days than routine care patients had. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
144
1
14

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(160 citation statements)
references
References 9 publications
1
144
1
14
Order By: Relevance
“…31 It is critical that the AHW feels supported, respected in their role and informed and competent with respect to relevant health information. Further, with research suggesting patients enrolled in programs using multidisciplinary teams will have significantly fewer hospital readmissions than routine care patients, 32 inclusion of the AHW in patient team management is critical. Such suitable acknowledgement within the hospital hierarchy is also likely to improve role effectiveness and has significant implications for staff retention.…”
Section: Recommendations For Improving the Ahw Role In Hospitalsmentioning
confidence: 99%
“…31 It is critical that the AHW feels supported, respected in their role and informed and competent with respect to relevant health information. Further, with research suggesting patients enrolled in programs using multidisciplinary teams will have significantly fewer hospital readmissions than routine care patients, 32 inclusion of the AHW in patient team management is critical. Such suitable acknowledgement within the hospital hierarchy is also likely to improve role effectiveness and has significant implications for staff retention.…”
Section: Recommendations For Improving the Ahw Role In Hospitalsmentioning
confidence: 99%
“…Studies showed that the elderly often had multiple diseases, which could cause limitation and dependence. (4) In this sense, it should be emphasized that health professionals must be prepared to assist the elderly in the organization of their care, with services that must be varied to meet their multiple needs. It is important to build networks of elderly care.…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3) In the last two decades, some researchers have conducted studies in order to identify aggravating factors in the health/disease status of the hospitalized patients, to improve the quality of care provided to them and also to reduce costs. (4)(5)(6) In this context, one of the proposals that can be a tool to improve communication within the interdisciplinary team, and to characterize the complexity of care for clinical, scientific and educational purposes, is the Interdisciplinary Medicine Instrument (INTERMED): a tool that can offer positive responses in assessing patients requiring care, and in helping adjust the provision of health services in general, and in mental health. (7) The validity of this instrument is documented for the care of several types of patients.…”
Section: Introductionmentioning
confidence: 99%
“…40 Effective multidisciplinary teams improve patient outcomes in chronic disease management, such as reducing readmissions from heart failure, and improving blood pressure control in those with hypertension. 41,42 Since a physician needs more than 20 hours per day to provide recommended care to a panel of primary care patients, working with an interprofessional team is essential to patient care today. 43 Collaboration.…”
Section: Priority Area 1: Team-based Carementioning
confidence: 99%